Optimization and development of a high-throughput TR-FRET screening assay for SLIT2/ROBO1 interaction - Somaya A. Abdel-Rahman; Moustafa T. Gabr (SLAS Discovery)
The SLIT2/ROBO1 signaling axis plays a critical role in cell migration, angiogenesis, and immune regulation, contributing to tumor progression, metastasis, and therapy resistance. SLIT2 is highly expressed in various malignancies, where it promotes immune evasion by recruiting tumor-associated macrophages and disrupting vascular integrity, ultimately diminishing therapeutic efficacy. Beyond cancer, SLIT2/ROBO1 is implicated in neural development, fibrosis, and vascular remodeling, making it a potential but underexplored therapeutic target. However, no small-molecule inhibitors of SLIT2/ROBO1 interaction currently exist. Herein, we describe the development and optimization of a time-resolved fluorescence resonance energy transfer (TR-FRET) assay for high-throughput screening of small-molecule inhibitors targeting this pathway. Using recombinant SLIT2 and ROBO1, we established a robust assay that enables high-throughput screening (HTS) of chemical libraries of small molecules for SLIT2/ROBO1 inhibition. Screening a focused chemical library of protein-protein interaction (PPI) inhibitors identified SMIFH2 as a SLIT2/ROBO1 inhibitor, demonstrating its ability to disrupt the interaction in a dose-dependent manner. Our study introduces a novel screening platform for identifying small molecule inhibitors of SLIT2/ROBO1, laying the foundation for future drug discovery efforts aimed at targeting this signaling axis in cancer and other diseases.